Pengaruh Social Culture dan Environmental Awareness terhadap Perilaku Islamic Green Computing (IGC) - Pasuna, Safitra Ramadhani; Yalina, Nita; Rozas, Indri Sudanawati (Program Studi Sistem Informasi Fakultas Sains dan Teknologi, UIN Sunan Ampel Surabaya, 2024)
Islamic Green Computing (IGC) is a concept of using Information Technology based on Islamic values effectively and efficiently. Religious, Economic, Gender, and Environmental Awareness research variables on Islamic Green Computing behavior. This data was obtained from 90 students using the UIN Sunan Ampel Surabaya Integration Laboratory based on the Slovin formula using simple random sampling technique. The method used is multiple linear regression analysis, producing Religious and Environmental Awareness significantly influence the behavior of Islamic Green Computing while the Economy and Gender have no significant effect on the application of Islamic Green Computing. Green Islamic Computing can be done by increasing the religiosity and environmental awareness of students, thus the application of the IGC concept can be done and applied well.